The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1039/d2ra00318j
|View full text |Cite
|
Sign up to set email alerts
|

Study of the mechanism of color change of prehnite after heat treatment

Abstract: Mechanism of color change of prehnite after heat treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…As the temperature continues to rise, the CaCO 3 starts to decompose and most of the calcium is present mainly in the form of silicates. The formation of CaSiO 3 could reduce the ash fusion temperature, while refractory minerals such as CaAl 2 Si 3 O 10 (OH) 2 decomposes below 900 • C, which further reduces the ash fusion temperature [27]. The effect of incineration temperature on the migration and transformation of magnesium is given in Figure 1d, and it is found that, in the low-temperature region, magnesium always coexists with calcium, and more magnesium silicate and magnesium oxide are formed as the temperature increases.…”
Section: Screening Of Potential Additive For Enhancing the Combustion...mentioning
confidence: 99%
“…As the temperature continues to rise, the CaCO 3 starts to decompose and most of the calcium is present mainly in the form of silicates. The formation of CaSiO 3 could reduce the ash fusion temperature, while refractory minerals such as CaAl 2 Si 3 O 10 (OH) 2 decomposes below 900 • C, which further reduces the ash fusion temperature [27]. The effect of incineration temperature on the migration and transformation of magnesium is given in Figure 1d, and it is found that, in the low-temperature region, magnesium always coexists with calcium, and more magnesium silicate and magnesium oxide are formed as the temperature increases.…”
Section: Screening Of Potential Additive For Enhancing the Combustion...mentioning
confidence: 99%